EVALUASI PENGGUNAAN DANA DESA TAHUN 2015 PADA BADAN PEMBERDAYAAN MASYARAKAT KAMPUNG DAN TRANSMIGRASI (BPMKT) KABUPATEN KEPULAUAN YAPEN,PAPUA - Pasodung, Olana Christin; Tinangon, Jantje J. (ACCOUNTABILITY, 2017)
For the welfare of the nation, the Government is determined to build Indonesia from the periphery to strengthen these areas and villages within the framework of the Unitary Republic of Indonesia. Indonesia build on the outskirts of the village it means to be constructed because the majority of the Indonesian population is no village. So, in building the village there are some things that need to be noticed, especially in the aspect of management / use of village funds, namely, the village fund should be used properly so that tangible results in the field can be seen according to the Government Work Plan Kampung (RKPK) that apply to each each village / villages in the district Yapen islands. In Serui are still many villagers whose lives have not been feasible. This means that the use of village funds in some villages, there penyelewangan funds in the field that are not in accordance with RKPK and legislation in force in Indonesia. Thus the need for regulatory oversight remained in the village fund management process to avoid abuses that occurred while in the field. This study aims to determine the use of funds Yapen Islands district villages in Papua has been run with the maximum or not according to the rules applicable legislation. Research type used is descriptive research including data collection form of description of the distribution process, management / use, supervision until accountability applied by the village fund 160 villages in Serui. Research on Community Empowerment Board Kampung and Transmigration (BPMKT) Yapen Islands is there are still many shortcomings in the village in a few villages in the use of funds of the village so the concrete manifestation of the results of the field went wrong RKPK and forms of accountability of the use of village funds have not been implemented in a timely manner. Thus the need for regulation that is still to organize activities to be undertaken by the villagers.Keywords: the use of village funds, Village Community Empowerment Board and Transmigration.